NFT and W. Benjamin: Regressive re-auraticization in new forms of digital collectionism - Migliorini, Anna (Scenari, 2022)
This article investigates the current question of NFTs, non-fungible tokens, by making an analysis from a philosophical perspective, based on Walter Benjamin’s reflections in the 1930s on “aura” (Das Kunstwerk im Zeitalter seiner technischen Reproduzierbarkeit). The analysis underlines economic, political, and environmental implications of this “form of art”, as well as its creation, collection, ownership, and exchange, reconducting to a new manifestation of materiality. NFTs may interrupt the relation with both the artistic technicality and the original authorship itself. They shift the attribution of the artistic character from the object to a new layer, but they fail to renew the artistic value in as much as they still depend on the art market, and as they apply a mechanism of scarsification that overlaps with the functioning of aura.